2004
DOI: 10.1097/01.aog.0000125869.78251.5e
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Micrometastases in Histologically Negative Lymph Nodes of Early-Stage Cervical Cancer Patients

Abstract: II-3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
3
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 16 publications
1
45
3
4
Order By: Relevance
“…Moreover, Van Trappen et al (4) also noted that 44% of pathologically-negative lymph nodes expressed CK19, and that early micrometastases occured in 50% of patients with cervical cancer. In this study the detection rate of micrometastases by IHC for detecting CK19 expresssion in pathological lymph nodes of cervical cancer was 24.6%, while Lentz et al (11), using similar method, index and materials, found micrometastases occurred in 15% of the patients and that the detection rate of micrometastases in lymph nodes was 0.9%, both of the percentages are lower than ours. The incidence rates of micrometastases in our study detected by ISH and IHC (60 and 46.6%, respectively) were also higher than that reported in other literature.…”
Section: Discussioncontrasting
confidence: 71%
“…Moreover, Van Trappen et al (4) also noted that 44% of pathologically-negative lymph nodes expressed CK19, and that early micrometastases occured in 50% of patients with cervical cancer. In this study the detection rate of micrometastases by IHC for detecting CK19 expresssion in pathological lymph nodes of cervical cancer was 24.6%, while Lentz et al (11), using similar method, index and materials, found micrometastases occurred in 15% of the patients and that the detection rate of micrometastases in lymph nodes was 0.9%, both of the percentages are lower than ours. The incidence rates of micrometastases in our study detected by ISH and IHC (60 and 46.6%, respectively) were also higher than that reported in other literature.…”
Section: Discussioncontrasting
confidence: 71%
“…Recently, sentinel lymph node biopsy has become common, and when these lymph nodes are negative for metastasis, many gynecologists omit the systematic lymphadenectomy. There are many benefits of this method, including low invasiveness and a low rate of complications [14,15], but Marchiole et al [16] reported that the sentinel lymph node biopsy method resulted in 14.3% false negatives, and Lentz et al [17] described that 15% of the negative sentinel nodes had micrometastasis. Therefore, a complete lymphadenectomy may be able to elevate the detection rate of LNM and may improve the prognosis in cases with 1 or 2 LNM sites.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LND significantly impacts postoperative treatment decisions in clinically early stage disease due to upstaging solely resulting from lymph node involvement. 2,7,14,[21][22][23][24][25][26] Therefore, the surgeon should make an effort to retrieve as many lymph nodes as possible even in obese patients. Unfortunately, obese women were less likely to undergo a surgical assessment of their lymph nodes than non-obese women in the past.…”
Section: -11mentioning
confidence: 99%